Sex Disparities in Sudden Cardiac Death. (18th August 2021) - Butters, Alexandra; Arnott, Clare; Sweeting, Joanna; Winkel, Bo Gregers; Semsarian, Christopher; Ingles, Jodie
Abstract : The overall incidence of sudden cardiac death is considerably lower among women than men, reflecting significant and often under-recognized sex differences. Women are older at time of sudden cardiac death, less likely to have a prior cardiac diagnosis, and less likely to have coronary artery disease identified on postmortem examination. They are more likely to experience their death at home, during sleep, and less likely witnessed. Women are also more likely to present in pulseless electrical activity or systole rather than ventricular fibrillation or ventricular tachycardia. Conversely, women are less likely to receive bystander cardiopulmonary resuscitation or receive cardiac intervention post-arrest. Underpinning sex disparities in sudden cardiac death is a paucity of women recruited to clinical trials, coupled with an overall lack of prespecified sex-disaggregated evidence. Thus, predominantly male-derived data form the basis of clinical guidelines. This review outlines the critical sex differences concerning epidemiology, cause, risk factors, prevention, and outcomes. We propose 4 broad areas of importance to consider: physiological, personal, community, and professional factors.